Hidroxialuminosilicatos e a biodisponibilidade do alumínio: avaliação in vivo - Kunz, Simone Noremberg (2012)
Aluminium (Al) and silicon (Si) are contaminants found in substances used in the parenteral nutrition (PN). Because of its large volume, nutrition and infusion solutions are pharmaceutical products parenterally administered, which present higher risks of adverse effects when contaminated. Insoluble and biologically inert species of hydroxyaluminosilicates (HAS) may be formed in solutions containing Al and Si when pH > 4.5. This chemical interaction is considered of great interest in biology because of its possible role in detoxification or protection against metal toxicity. In this study the Al bioavailability was investigated in the presence of Si and some PN components in vivo. Al and Si body distribution in Wistar rats was analyzed after 60 administrations of Al 0.5 mg/kg/day and/or Si 2 mg/kg/day in the presence or absence of calcium gluconate or potassium dihydrogenphosphate in concentrations similar to those used in the PN solutions. δ -Aminolevulinic acid dehydratase enzyme activity and tiobarbituric acid reactive species (TBARS) content was also evaluated in animal tissues. Tissue digestion methods were optimized for the determination of both Al and Si in the same samples by Graphite Furnace Atomic Absorption Spectrometry (GFAAS). Better Al and Si recoveries in animal tissue samples occurred after dissolution with tetramethylammonium hydroxide (TMAH) using Si 15 mg/L as modifier for Al determination and Pd 2 g/L for Si. Before the measurements, graphite furnace was coated with Zr following a specific heating program. Al accumulated in all tissues, especially in the liver, kidneys, bones and blood. Si decreased Al accumulation, this effect was less pronounced in the presence of PN components though. Si tissue accumulation was also observed, mainly when administered together with phosphate. Although Al was deposited in the tissues, pronounced toxicity effects were not observed. Increase in lipidic peroxidation was observed in a few tissues. When δ-ALA-D activity was altered, it was increased in Al treated groups, mainly in Ca gluconate treatment. As a conclusion, Si did not decrease Al deposition and therefore the metal biodisponibility amidst the NP components.